The effect and mechanism of current injection to suppress light and elevated temperature induced degradation in p-type cast-mono and multicrystalline silicon Passivated Emitter and Rear cells. (15th March 2022) - Hu, Zechen; Song, Lihui; Lin, Dehang; Zhao, Tong; He, Qiyuan; Yuan, Shuai; Yu, Xuegong; Yang, Deren
Highlights: The effective approach to suppress LeTID in Cast-Mono silicon and multicrystalline silicon PERC by current injection and annealing is proposed, with the minimized V oc degradation to only ∼ 0.2 %rel for CM-Si PERC and ∼ 0.3 %rel for mc-Si PERC during prolonged stability test. The dependence of LeTID suppression in cast grown silicon PERC upon applied injection currents and annealing temperatures is studied. A potential mechanism for current injection and annealing to suppress LeTID in cast grown silicon PERC is discussed. Abstract: In this work, we demonstrate that the forward current injection together with annealing as pre-treatment can dramatically suppress V oc degradation in both p -type Cast-Mono silicon (CM-Si) and multicrystalline silicon (mc-Si) Passivated Emitter and Rear Cells (PERC) during the following prolonged Light and elevated Temperature Induced Degradation (LeTID) stability test. To explore the underlying mechanisms, the dependence of the suppression extent of the V oc degradation upon applied currents and temperatures is studied. Interestingly, it is found that the modest injected current and annealing temperature are best for cell performance, leading to an evident increase (up to ∼ 0.4 %rel ) in V oc as well as the degradation extent during LeTID stability test can be minimized to only ∼ 0.2 %rel and ∼ 0.4 %rel for CM-Si and mc-Si PERC, respectively. This result is based on large number of commercial cells and therefore shows huge potential for application into mass production and may be of significance to the global photovoltaic industry. Finally, a qualitative model based on the different states and behaviors of the potential participants - hydrogen, is proposed to explain the underlying mechanisms of LeTID and anti-LeTID behaviors in CM-Si and mc-Si.